Influence of the vegetation period on the spread of economically important viral diseases in Burley tobacco - Y. Yonchev; N. Keranova (Trakia Journal of Sciences)
The present study explores the influence of the vegetation period of Burley tobacco on the spread of viruses such as TMW, PVY-Complex, CMV / PVY-Complex, TSWV and CMV. To establish this relation, a correlation analysis is applied and the proven effects are represented by linear regression models. In 2014, the number of days from replanting has a strong positive impact on the percentage of plants infected by PVY-Complex (0.985**) as well as by TMV (0.781*). For 2015, the very strong effect was only seen on CMV / PVY-Complex (0.976**). In 2016, the duration of the period had a positive effect on the spread of CMV / PVY-Complex (0.868*), CMV (0.904 **) and TSWV (0.966**). In 2017 there is a very strong positive correlation between PVY-Complex (0.885*), CMV (0.948**) and TSWV (0.955**) on one hand and the planting period on the other. As a result of the conducted study over the entire four-year period, it has been proven that during the first two years the increase in the vegetation period leads to an increase in the incidence of PVY complex. During the second half of the analyzed period, CMV and TSWV are proved to be affected by the length of the time from the replanting.